(untitled) (Acta Scientiarum. Animal Sciences, 2017)
This study simulated acidic habitat for different life stages of Clarias gariepinus to know the effect on survival, mortality, morphology and behaviour. The fish were exposed to pHs 3, 4, 5, 6 and 8.01 (control) for 35 days. 100% mortality was recorded for all the life stages in pH 3, and 80, 62 and 36% of mortality of fingerlings, juveniles and adults respectively were recorded in pH 4. In pH 5, 30, 26 and 12% mortalities of fingerlings, juveniles and adults respectively were recorded and at pH 6 mortalities of fingerlings, juveniles and adults were 12, 10 and 4% respectively. Control pH mortalities were 10, 6 and 2% for fingerlings, juveniles and adults respectively. Mortality was due to lack of oxygen uptake, stress and circulatory collapse. All these elicited the behavioural responses and morphological abnormalities like erratic swimming, gasping, dark body colouration and lethargy. The study showed that different life stages of C. gariepinus tolerate different acidic pH waters, with high mortalities of the fingerlings, juveniles and adults in pHs 3, pH 4 is sub-lethal to fingerlings, juveniles and adult, pH 5 sub-lethal to fingerlings and sub-optimal for juveniles, and pH 6 optimal for all life stages.